Properties and Developments of Combustion and Gasification of Coal and Char in a CO2-Rich and Recycled Flue Gases Atmosphere by Rapid Heating - Zhigang Li; Xiaoming Zhang; Yuichi Sugai; Jiren Wang; Kyuro Sasaki (Journal of Combustion)
Combustion and gasification properties of pulverized coal and char have been investigated experimentally under the conditions of high temperature gradient of order 200°C·s−1 by a CO2 gas laser beam and CO2-rich atmospheres with 5% and 10% O2. The laser heating makes a more ideal experimental condition compared with previous studies with a TG-DTA, because it is able to minimize effects of coal oxidation and combustion by rapid heating process like radiative heat transfer condition. The experimental results indicated that coal weight reduction ratio to gases followed the Arrhenius equation with increasing coal temperature; further which were increased around 5% with adding H2O in CO2-rich atmosphere. In addition, coal-water mixtures with different water/coal mass ratio were used in order to investigate roles of water vapor in the process of coal gasification and combustion. Furthermore, char-water mixtures with different water/char mass ratio were also measured in order to discuss the generation ratio of CO/CO2, and specified that the source of Hydrocarbons is volatile matter from coal. Moreover, it was confirmed that generations of CO and Hydrocarbons gases are mainly dependent on coal temperature and O2 concentration, and they are stimulated at temperature over 1000°C in the CO2-rich atmosphere.